PERBEDAAN KEKASARAN PERMUKAAN BASIS RESIN AKRILIK POLIMERISASI PANAS MENGGUNAKAN BAHAN PUMIS, CANGKANG TELUR DAN PASTA GIGI SEBAGAI BAHAN POLES - Syafrinani Syafrinani; Yudi Setiawan (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2017)
Denture base widely were made from heat polymerized acrylic resin. Either one of physical properties on this material must be concern is surface roughness, rough surface could interfere patient’s comfort, and microbial colonization. Therefore polishing procedure were needed, polishing material that mostly used on acrylic resin was pumice, there is another alternative material i.e eggshell and toothpaste because had abrasive ability. The aim of this research is to determine the difference surface roughness of heat polymerized acrylic denture base resin used pumice, eggshell and toothpaste as polishing materials. The design research in this study is laboratory experimental with rectangle sample with size 50 x 20 x 3 ±1 mm. There are 30 samples for 3 groups. The result of this research shows a significant difference between pumice group and eggshell group with p value = 0,0001 (p < 0,05), pumice and toothpaste with p value = 0,0001 (p < 0,05), egghsell and toothpaste with p value = 0,032 (p < 0,05). Polishing that used an alternative material from eggshell and toothpaste produce lower surface roughness score rather than pumice.